The Role of Sport in Shaping Gender Identity of FIK Unimed Students - Sitanggang, Indah Swira; Zaluku, Intan Kartika F; Sipayung, Cindy Vini Rosen; Saragih, Rama Suranta; Lubis, Amirsyah Putra (Journal Coaching Education Sports, 2025)
Introduction: Promoting gender equality by understanding gender constructs is crucial to eradicating gender discrimination and creating a more equitable society. A person's masculinity and femininity can be influenced by what they see in their daily lives, including through sporting activities. Methods: This study used quantitative methods with the main instruments being questionnaires and documentation. Questionnaires were used to collect data on students' perceptions, attitudes, and level of knowledge about the role of sports in shaping gender identity. Respondents in this study were 30 FIK Unimed students who were purposively selected. Results: The data obtained from the questionnaire will be analyzed to identify the pattern of students' perceptions of the role of sports in shaping their masculinity and femininity. The results of this study are expected to provide new insights into the influence of sports in the construction of gender identity among students. Discussion: The results of this study will be analyzed to understand how sport, as an activity that is often associated with a particular gender, affects the gender identity formation of FIK Unimed students. The discussion will also address the social implications of the research findings to promote gender equality in sport and education.